Yeast chemotropism: A paradigm shift in chemical gradient sensing. Issue 2 (3rd April 2017) - Ismael, Amber; Stone, David E.
ABSTRACT: The ability of cells to direct their movement and growth in response to shallow chemical gradients is essential in the life cycles of all eukaryotic organisms. The signaling mechanisms underlying directional sensing in chemotactic cells have been well studied; however, relatively little is known about how chemotropic cells interpret chemical gradients. Recent studies of chemotropism in budding and fission yeast have revealed 2 quite different mechanisms — biased wandering of the polarity complex, and differential internalization of the receptor and G protein. Each of these mechanisms has been proposed to play a key role in decoding mating pheromone gradients. Here we explore how they may work together as 2 essential components of one gradient sensing machine.